Brivanib Exhibits Potential for Pharmacokinetic Drug-Drug Interactions and the Modulation of Multidrug Resistance through the Inhibition of Human ABCG2 Drug Efflux Transporter and CYP450 Biotransformation Enzymes - Hofman, Jakub; Sorf, Ales; Vagiannis, Dimitrios; Sucha, Simona; Kammerer, Sarah; Küpper, Jan-Heiner; Chen, Si; Guo, Lei; Ceckova, Martina; Staud, Frantisek (Molecular pharmaceutics, 2019)
Brivanib, a promising tyrosine kinase inhibitor, is currently undergoing advanced stages of clinical evaluation for solid tumor therapy. In this work, we investigated possible interactions of this novel drug candidate with ABC drug efflux transporters and cytochrome P450 (CYP450) drug-metabolizing enzymes that participate in cancer multidrug resistance (MDR) and pharmacokinetic drug-drug interactions (DDIs). First, in accumulation experiments with various model substrates, we identified brivanib as an inhibitor of the ABCB1, ABCG2, and ABCC1 transporters. However, in subsequent combination studies employing 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide proliferation assays in both Madin-Darby canine kidney II (MDCKII) and A431 cellular models, only ABCG2 inhibition was revealed to be able to synergistically potentiate mitoxantrone effects. Advantageous to its possible use as MDR antagonist, brivanib's chemosensitizing properties were not impaired by activity of any of the MDR-associated ABC transporters, as observed in comparative viability assay in the MDCKII cell sublines. In incubation experiments with eight recombinant CYP450s, we found that brivanib potently inhibited CYP2C subfamily members and the CYP2B6 isoform. Finally, in induction studies, we demonstrated that brivanib upregulated ABCB1 and CYP1A2 messenger RNA levels in systemic cell models, although this interaction was not significantly manifested at a functional level. In conclusion, brivanib exhibits potential to cause clinically relevant pharmacokinetic DDIs and act as a modulator of ABCG2-mediated MDR. Our findings might be used as an important background for subsequent in vivo investigations and pave the way for the safe and effective use of brivanib in oncological patients.
Keywords: Alanine; nádorové proteiny; Cell Line; Biotransformation; lékové interakce; Dogs; alanin; buňky MDCK; inhibitory cytochromu P450; ATP Binding Cassette Transporter, Subfamily G, Member 2; chemorezistence; Cytochrome P-450 Enzyme Inhibitors; triaziny; P-glykoproteiny; Madin Darby Canine Kidney Cells; mnohočetná léková rezistence; systém (enzymů) cytochromů P-450; Animals; biotransformace; lidé; Cytochrome P-450 Enzyme System; ABC transportér z rodiny G, člen 2; Drug Interactions; zvířata; Humans; Triazines; Neoplasm Proteins; buněčné linie; Drug Resistance, Multiple; psi; ATP Binding Cassette Transporter, Subfamily B; Drug Resistance, Neoplasm